1992
DOI: 10.1002/bjs.1800790319
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastasis from early gastric cancer: endoscopic resection of tumour

Abstract: The clinicopathological features of 748 solitary early gastric cancers were examined with regard to lymph node metastasis. Among several factors, only depth of invasion and tumour size correlated significantly with node involvement. Tumours which satisfy the following criteria may not metastasize to lymph nodes: (1) confined to the mucosa; (2) less than 1.5 cm in diameter; (3) macroscopically elevated; (4) macroscopically depressed, without intramural ulcers or ulcer scars (endoscopically, no fold convergence)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
205
1
18

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(234 citation statements)
references
References 8 publications
10
205
1
18
Order By: Relevance
“…In the present study, massive sm invasion was particularly frequent when EGCs mimicking AGCs also had lymph node metastasis. This result is explainable by the observation that the submucosal layer of the stomach is rich in lymphatic capillaries (Inoue et al, 1991;Maehara et al, 1992;Sano et al, 1992). We showed that 60% of EGCs simulating AGC had sm3 invasion, whereas 24% of the other EGCs had sm3 invasion.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, massive sm invasion was particularly frequent when EGCs mimicking AGCs also had lymph node metastasis. This result is explainable by the observation that the submucosal layer of the stomach is rich in lymphatic capillaries (Inoue et al, 1991;Maehara et al, 1992;Sano et al, 1992). We showed that 60% of EGCs simulating AGC had sm3 invasion, whereas 24% of the other EGCs had sm3 invasion.…”
Section: Methodssupporting
confidence: 60%
“…Above all, it is worth mentioning that the frequency of lymph node metastasis was similar in the two groups. Lymph node metastasis is the most reliable prognostic factor in gastric cancers when the depth of invasion is similar (Maruyama et al, 1987;Hioki et al, 1990;Maehara et al, 1992;Sano et al, 1992 Recent advances in diagnostic techniques allowed us to determine preoperative and intraoperative staging of gastric cancer (Tatsuta et al, 1982;Yasuda et al, 1986;Tio et al, 1989). In particular, endoscopic ultrasonography and intraoperative histological examination are useful for more objective determination of the depth of invasion for gastric cancer, which is strongly correlated with patients' survival time (Maruyama et al, 1989;Kitamura et al, 1996c).…”
Section: Methodsmentioning
confidence: 99%
“…In the present CK-immunohistochemical study, tumor size, deep invasion to the submucosa, lymphatic invasion, vascular invasion, and poor differentiation of the tumor were five important risk factors correlated with lymph node involvement in EGC detected by CK-immunostaining. Histologically, metastasis to the lymph node was extremely rare in tumors with a diameter of less than 2 cm [2,7]. We also found that tumors with a diameter of more than 2 cm more frequently metastasized to the lymph nodes, and most of these involvements were in the form of clusters of cancer cells in the lymph nodes.…”
Section: Discussionsupporting
confidence: 49%
“…Recent improvements in endoscopic techniques and the widespread use of mass screening have made it possible to detect gastric cancer at a very early stage, and have led to excellent outcomes for patients after surgical treatment [2][3][4]. Although gastrectomy with D2 lymphadenectomy has been the standard treatment for early gastric cancer [5][6][7], a less invasive surgerical prodecure without lymphadenectomy has recently been used to treat these patients and has achieved not only complete cure of the disease but also a better postoperative quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic treatment for patients with early-stage gastric carcinoma has been widely used for curative therapy, and such endoscopic tumour resection has enabled patients with gastric cancer to have better prognoses (Haruma et al, 1990;Sano et al, 1992;Amano et al, 1998). Although ESD is a useful method newly developed not only for endoscopic curative resection of EGCs but also for accurate histological diagnosis, the indications for such endoscopic treatment are limited to small, well-differentiated adenocarcinomas with minimal submucosal invasion (Hirasaki et al, 2005;Kato, 2005).…”
Section: Discussionmentioning
confidence: 99%